2015
DOI: 10.1128/mcb.01521-14
|View full text |Cite
|
Sign up to set email alerts
|

The Human RNA Polymerase I Transcription Terminator Complex Acts as a Replication Fork Barrier That Coordinates the Progress of Replication with rRNA Transcription Activity

Abstract: In S phase, the replication and transcription of genomic DNA need to accommodate each other, otherwise their machineries collide, with chromosomal instability as a possible consequence. Here, we characterized the human replication fork barrier (RFB) that is present downstream from the 47S pre-rRNA gene (ribosomal DNA [rDNA]). We found that the most proximal transcription terminator, Sal box T1, acts as a polar RFB, while the other, Sal box T4/T5, arrests replication forks bidirectionally. The fork-arresting ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 54 publications
(66 reference statements)
4
64
0
Order By: Relevance
“…Studies on budding yeast rDNA have identified the existence of natural Replication Fork Barriers (RFBs), replication pause sites defined by specific DNA sequences that bind to non-nucleosomal proteins, blocking replication fork progression in the opposite direction to transcription and acting as recombinational hotspots 65-67 . RFB-mediated mechanisms at rDNA loci to block replication in case of converging transcription, preventing head-on collisions between replication and transcription, have been identified in many organisms, including murine and human cells 64,68,69 . Centromeres are also loci that are difficult to replicate due to their heterochromatic nature and richness in repetitive sequences 70 .…”
Section: Dna Replication Program and The Causes Of Replication Stressmentioning
confidence: 99%
“…Studies on budding yeast rDNA have identified the existence of natural Replication Fork Barriers (RFBs), replication pause sites defined by specific DNA sequences that bind to non-nucleosomal proteins, blocking replication fork progression in the opposite direction to transcription and acting as recombinational hotspots 65-67 . RFB-mediated mechanisms at rDNA loci to block replication in case of converging transcription, preventing head-on collisions between replication and transcription, have been identified in many organisms, including murine and human cells 64,68,69 . Centromeres are also loci that are difficult to replicate due to their heterochromatic nature and richness in repetitive sequences 70 .…”
Section: Dna Replication Program and The Causes Of Replication Stressmentioning
confidence: 99%
“…Sal boxes recruit TTF-1, the mammalian ortholog of S. pombe Reb1, which is involved in termination of pre-mRNA transcription [64]. As is the case for S. pombe Swi1 and S. cerevisiae Tof1, human Timeless is required for replication fork arrest at RFBs to coordinate the progression of replication with transcription activity in HeLa cells (Figure 2C) [65]. Thus, the role of the FPC at these pausing sites is conserved between yeast and mammalian cells.…”
Section: Replication Barriers Associated With Repeat Dna and Protementioning
confidence: 99%
“…Deletion of both tof1 and rrm3 , restores pausing to a level significantly higher than that of the wild-type cells [68]. Furthermore, Timeless–Tipin homologs in S. cerevisiae, S. pombe , and humans control the RFBs of rDNA genes in order to prevent collisions between transcription and replication complexes during ribosomal gene transcription [39,65,68,224], suggesting the general role of Timeless–Tipin in preventing genome instability at the interface of DNA replication and transcription (Figure 7). …”
Section: Coordination Between Transcription and Replication Machinmentioning
confidence: 99%
“…An RFB has also recently been described in the human rDNA repeat (Akamatsu and Kobayashi 2015), and IGS transcripts have been observed in humans and mice in response to various nucleolar stresses or replication senescence (Audas et al 2012;Bierhoff et al 2014). The degree to which the model proposed for yeast can be extended to human cells is an open question.…”
Section: Ganley 2005)mentioning
confidence: 99%
“…The IGS houses gene promoters and regulatory elements, such as spacer promoters and repetitive enhancer elements, which control pre-rRNA synthesis (Goodfellow and Zomerdijk 2013). The IGS also contains replication origins and replication fork barriers (RFBs) that prevent collisions between the replication and transcription machineries (Brewer et al 1992;Kobayashi et al 1992;Akamatsu and Kobayashi 2015). Finally, under certain circumstances, such as stress, loss of repressive chromatin modifications, replicative senescence, or aging, the IGS can be transcribed by RNA Pol II (Earley et al 2010;Audas et al 2012;Saka et al 2013;Bierhoff et al 2014).…”
Section: Rdna Arrays and Norsmentioning
confidence: 99%